Copper-cobalt doped graphene MOF composite material and preparation method and application thereof

The preparation of copper-cobalt-doped graphene MOF composite material by solvent thermal synthesis has solved the problem of insufficient reactive activity and stability of existing MOF materials, and achieved efficient adsorption and photocatalytic degradation of pollutants in organic wastewater.

CN119793426AActive Publication Date: 2025-04-11TANGSHAN COLLEGE
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510028581.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing MOF materials have weak reactivity and reaction stability when treating wastewater containing MB, making it difficult to effectively remove dyes.

Method used

The copper-cobalt-doped graphene MOF composite material was prepared by solvent thermal synthesis to form an octahedral porous structure with a large specific surface area and pore volume, and was used for efficient adsorption and photocatalytic degradation of organic wastewater.

Benefits of technology

It has achieved efficient adsorption and photocatalytic degradation of pollutants such as MB, phenol, tetracycline and catechol in organic wastewater, significantly improving the adsorption performance and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793426A_ABST
    Figure CN119793426A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of wastewater treatment, and particularly discloses a copper-cobalt-doped graphene MOF composite material and a preparation method and application thereof.The graphene-doped bimetallic copper-cobalt MOF composite material is successfully prepared through a solvothermal synthesis method, is of an octahedral porous structure and has the very large specific surface area and pore volume, and the specific surface area and the pore volume are large; the organic wastewater can be efficiently adsorbed and photocatalytically degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of wastewater treatment, and in particular to a copper-cobalt doped graphene MOF composite material and a preparation method and application thereof. Background Art

[0002] Metal-organic frameworks (MOFs) consist of metal centers and organic linkers to form an infinite crystalline network. MOF materials are the main candidate materials for photocatalysts and adsorbents due to their unique pore structure, adjustable pore size, diverse adsorption sites, high specific surface area and porosity. For example, a widely studied copper-based MOF, HKUST-1, was discovered relatively early. Material characterization and experimental data (such as Langmuir isotherm and Gibbs free energy function) confirmed its potential application value in the treatment of MB-containing wastewater. This material spontaneously adsorbs MB with enthalpy change as the main driving force. Interestingly, HKUST-1 can be easily regenerated and maintain its adsorption capacity after washing with ethanol. Therefore, HKUST-1 may be one of the most promising candidates for dye removal. However, in the in-depth research and further promotion of application, it shows problems such as weak reactivity and reaction stability.

[0003] In order to improve the adsorption of pollutants by MOF, it has been proposed to incorporate a second metal ion for the synthesis of bimetallic MOF (BMOF). Hasan et al. emphasized the interaction mechanism between pollutants and MOF. The adsorption is carried out through a variety of different mechanisms, such as electrostatic interaction, acid-base interaction, hydrogen bonding, π-π interaction and hydrophobic interaction. Sometimes multiple interactions may occur in some specific adsorption processes. When the metal ion constant of a single metal MOF is low, the interaction of metal cations is weak. The synergistic effect shown by BMOF between the two metals reduces the activation energy of the reaction, which improves the performance of BMOF compared with either of the two single metal counterparts. Alloying can significantly improve the catalytic activity and stability, which is attributed to the rearrangement of the electronic structure, and the valence electrons will be reconfigured in the new potential field formed by different metal cores. The synthesis of bimetallic MOF changes the external surface properties and internal pore structure of the single metal MOF, produces new active metal sites, and thus enhances the adsorption performance. Compared with single metal MOF and zeolite, bimetallic MOF exhibits stronger fluid stability and desulfurization ability. Another outstanding property of bimetallic organic frameworks is their enormous structural tunability, which many semiconductor-based photocatalysts do not possess.

[0004] Graphene is an atomically thin planar carbon film whose enormous potential has attracted widespread attention in various fields since it was first produced by mechanical exfoliation in 2004. In addition to its size and shape, graphene also has a variety of outstanding chemical and physical properties. Graphene has high thermal conductivity, high flexibility, high transparency, excellent carrier mobility, ultra-high strength, extremely high theoretical specific surface area, excellent environmental compatibility, high mechanical strength, low production cost, and high adsorption capacity for organic and inorganic molecules.

[0005] Currently, many different semiconductors have been commonly used to couple with graphene for different applications and photocatalysis. Generally, these semiconductors can be divided into five types, namely inorganic and organic (metal-free gC 3 N 4 , metal organic frameworks (MOFs) and dyes) semiconductors and plasma metals. Graphene has ultra-high specific surface area, high conductivity and excellent mechanical properties, while MOF has large porosity, special pore structure and highly adjustable chemical properties. Combining the two into a composite material, graphene can be used as an excellent platform for growing MOF, which can not only play their respective advantages, but also has excellent performance in catalysis, adsorption, energy storage and other fields.

[0006] Therefore, it is urgent to study whether copper-cobalt-doped graphene MOF composites can be used for adsorption and photocatalytic degradation of organic wastewater. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a copper-cobalt doped biochar graphene MOF composite material and a preparation method and application thereof.

[0008] To achieve the above object, the present invention is implemented according to the following technical solutions: One of the purposes of the present invention is to provide a method for preparing a copper-cobalt doped graphene MOF composite material, comprising the following steps: Take Co(NO) in a molar ratio of (4-5):(1-2) 3 ) 2 ﹒ 6H 2 O and Cu (NO 3 ) 2 0.74 g of biochar and 0.1 g of graphene were added and mixed and dissolved in 25 ml of anhydrous ethanol. After magnetic stirring at room temperature for 1 h, the mixture was poured into a high-pressure reactor and treated by solvothermal synthesis at 160 ° C for 6 h. The mixture was cooled and centrifuged. The solid after centrifugation was cross-washed twice with DMF and anhydrous ethanol and dried to obtain a biochar graphene / copper-cobalt bimetallic MOF composite material.

[0009] Furthermore, after washing, the mixture was dried at 60° C. for 12 h.

[0010] The second object of the present invention is to provide a copper-cobalt doped biochar graphene MOF composite material prepared by the above method.

[0011] The third object of the present invention is to provide a copper-cobalt doped biochar graphene MOF composite material for use in the adsorption and photocatalytic degradation of organic wastewater.

[0012] Compared with the prior art, the present invention successfully prepared a biochar graphene-doped bimetallic copper-cobalt MOF composite material by a solvent thermal synthesis method, which exhibits an octahedral porous structure, has a very large specific surface area and pore volume, and can efficiently adsorb and photocatalytically degrade organic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 XRD spectra of graphene / Cu-Co-MOF with different doping ratios.

[0014] Figure 2 SEM images of graphene / 4Cu-2Co-MOF: (a) is magnified 20,000 times; (b) is magnified 15,000 times.

[0015] Figure 3 This is the adsorption-desorption curve of graphene / 4Cu-2Co-MOF.

[0016] Figure 4 This is the pore size distribution diagram of graphene / 4Cu-2Co-MOF.

[0017] Figure 5 The graphene / MOF ultraviolet diffuse reflection absorption spectrum: (a) is the graphene / MOF ultraviolet diffuse reflection absorption spectrum; (b) is the graphene / MOF bandgap width diagram.

[0019] Figure 6 This is the adsorption diagram of graphene / copper-cobalt bimetallic organic framework composite material.

[0020] Figure 7 This is a diagram showing the adsorption-photocatalytic synergistic removal of methylene blue by graphene / copper-cobalt bimetallic organic framework composite materials.

[0021] Figure 8 This is a diagram of the phenol adsorption effect of graphene / copper-cobalt bimetallic organic framework composite material.

[0022] Fig. 9 This is a diagram showing the catalytic degradation of phenol by graphene / copper-cobalt bimetallic organic framework composite material.

[0023] Fig.10 This is a diagram showing the catalytic degradation of tetracycline / catechol by graphene / copper-cobalt bimetallic organic framework composite material.

[0024] Fig.11 This is the effect diagram of graphene / copper-cobalt bimetallic organic framework composite material degrading simulated organic wastewater. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0026] Example 1

[0027] Weigh 0.29 g Co(NO 3 ) 2 ﹒ 6H 2 O, 0.94 g Cu (NO 3 ) 2 The mixture was mixed with 0.74 g of trimesic acid and 0.1 g of graphene and dissolved in 25 ml of anhydrous ethanol. After magnetic stirring at room temperature for 1 h, it was poured into a high-pressure reactor and treated with a solvothermal synthesis method (the solvent is water) at 160 ° C for 6 h. After cooling, it was centrifuged. The solid after centrifugation was cross-washed twice with DMF and anhydrous ethanol, and finally dried at 60 ° C for 12 h. After drying, a graphene / copper-cobalt bimetallic MOF composite material was obtained, which was recorded as graphene / 5Cu-1Co-MOF.

[0028] Example 2

[0029] Weigh 0.59 g Co(NO 3 ) 2 ﹒ 6H 2 O, 0.75 g Cu (NO 3 ) 2 0.74 g of biochar and 0.1 g of graphene were mixed and dissolved in 25 ml of anhydrous ethanol. After magnetic stirring at room temperature for 1 h, the mixture was poured into a high-pressure reactor and subjected to solvothermal synthesis (the solvent was water) at 160 °C for 6 h. The mixture was cooled and centrifuged. The solid after centrifugation was cross-washed twice with DMF and anhydrous ethanol and finally dried at 60 °C for 12 h. After drying, a graphene / copper-cobalt bimetallic MOF composite material was obtained, which was recorded as graphene / 4Cu-2Co-MOF.

[0030] Example 3

[0031] Weigh 0.29 g Co(NO 3 ) 2 ﹒ 6H 2 O, 0.75 g Cu (NO 3 ) 20.74 g of biochar and 0.1 g of graphene were mixed and dissolved in 25 ml of anhydrous ethanol. After magnetic stirring at room temperature for 1 h, the mixture was poured into a high-pressure reactor and subjected to solvothermal synthesis (the solvent was water) at 160 °C for 6 h. The mixture was cooled and centrifuged. The solid after centrifugation was cross-washed twice with DMF and anhydrous ethanol and finally dried at 60 °C for 12 h. After drying, a graphene / copper-cobalt bimetallic MOF composite material was obtained, which was recorded as graphene / 4Cu-1Co-MOF.

[0032] Comparative Example 1 0.75 g Cu(NO 3 ) 2 Mix with 0.74g biochar and dissolve in 25ml anhydrous ethanol, stir with a magnetic stirrer at room temperature for 1h, pour into a high-pressure reactor after stirring, tighten the reactor, put the reactor into an electric blast drying oven at 160℃ for solvent thermal synthesis (solvent is water) for 6h, cool and centrifuge the product in the reactor, cross-wash the solid with DMF and anhydrous ethanol twice, and finally put it into an electric blast drying oven for drying at 60℃ for 12h. Cu-MOF can be obtained after drying.

[0033] Comparative Example 2 1.16 g Co(NO 3 ) 2 ﹒ 6H 2 O and 0.74g biochar were mixed and dissolved in 25ml anhydrous ethanol, stirred at room temperature with a magnetic stirrer for 1h, poured into a high-pressure reactor after stirring, and the reactor was tightened and placed in an electric hot air drying oven for solvothermal synthesis (solvent: water) at 160°C for 6h. After cooling, the product in the reactor was centrifuged using a centrifuge, and the solid after centrifugation was cross-washed twice with DMF and anhydrous ethanol, and finally placed in an electric hot air drying oven for drying at 60°C for 12h. Co-MOF was obtained after drying.

[0034] X-ray diffraction (XRD) can analyze the long-range structure of crystalline materials and the short-range structure of amorphous materials, and infer the lattice constant, grain size, crystallinity and crystal defects of the crystal. This example uses an X-ray diffractometer from Rigaku Corporation of Japan, with a specification model of Smartlab SE and an instrument power of 3Kw, at 2 In the scanning range of =10°-90°, XRD tests were carried out on graphene / 5Cu-1Co-MOF, graphene / 4Cu-1Co-MOF, graphene / 4Cu-2Co-MOF, Cu-MOF, and Co-MOF at a scanning rate of 5° / min.

[0035] Test results such as Figure 1 As shown by Figure 1It can be seen that Cu-MOF at 2 There is no phase separation or other impurities at 11.65˚, 13.4˚, 17.4˚, 19˚, etc., and the crystallinity is good, indicating that Cu-MOF is successfully synthesized. However, Co-MOF has many impurity peaks, indicating that the crystallinity of the material Co- is not good. Compared with Cu-MOF, the graphene MOF composite material has an additional peak at 29.5˚.

[0036] SEM uses a high-energy electron beam to scan the sample, and then processes the generated physical information into an image, thereby achieving the characterization of the microscopic morphology of the material. This embodiment uses a field emission scanning electron microscope from JEOL, with a specification model of JSM-7900F, a magnification of 25 to 1,000,000 times (film magnification), and an acceleration voltage range of 0.01 kV to 30 kV. Graphene / 4Cu-2Co-MOF is sprayed with gold and then tested.

[0037] Test results such as Figure 2 As shown by Figure 2 From (a) and (b), we can see that graphene / 4Cu-2Co-MOF has octahedral, spherical and irregular polyhedral structure crystals. The formed regular octahedron has a similar morphology to Cu-BTC, indicating that the incorporation of Co did not destroy the crystal structure of Cu-BTC. It can be seen that many gaps are formed between the various particles, which are conducive to the adsorption of dyes and the photocatalytic activity of the samples, but both materials have agglomeration phenomenon.

[0038] The testing principle of BET is based on the adsorption of gas on the solid surface. The method is to first adsorb a certain amount of gas on the surface of the substance to be tested, and then determine the volume and pressure of the adsorbed gas to find its surface area. This method can measure the specific surface area of ​​the material, as well as the pore size distribution of micropores and mesopores, so as to evaluate the pore structure characteristics of the material. This embodiment uses the specific surface area and porosity tester of McMeretic Instruments Co., Ltd., the instrument model is 3FLEX, weigh about 0.7g of the sample, degas for 24h, and measure graphene / 5Cu-5Co-MOF at 80°C.

[0039] Test results such as Figure 3 , Figure 4 As shown by Figure 3 It can be seen that the specific surface area and porosity tester test results show that the specific surface area of ​​graphene / 5Cu-1Co-MOF is 315.4321 m² / g, the pore volume is 0.169035 cm³ / g, and the average pore diameter is 5.6489nm. Figure 3It can be seen that the adsorption and desorption curves of graphene / 5Cu-1Co-MOF are all type I adsorption isotherms, and the hysteresis loop is very weak, indicating the rich existence of micropores. The pore size range of micropores is 0.2-2nm, and the pore size range of mesopores is 2-50nm. Figure 4 It can be seen that the pore size of graphene / 4Cu-2Co-MOF is mostly in the range of 0.2nm and 20nm, indicating that micropores and mesopores exist simultaneously in graphene / 4Cu-2Co-MOF. This multi-level pore structure is conducive to good mass / charge transfer. At the same time, the BJH pore size distribution diagram of graphene / 4Cu-2Co-MOF is denser, indicating that the porosity of the composite material is higher, which is consistent with the test results.

[0040] UV-Vis DRS measures, analyzes and infers the composition, content and structure of a substance based on the characteristics of the selective absorption and reflection of light by the substance being tested. It is also applied to the absorption properties, structure, valence state, coordination symmetry and other aspects of solid materials. This experiment used the SolidSpec-3700 UV-visible-infrared spectrometer manufactured by Japan's Kyoto Corporation. The detection was carried out in the range of 200~800nm, and the graphene / 5Cu-1Co-MOF, graphene / 4Cu-1Co-MOF, and graphene / 4Cu-2Co-MOF were measured after tableting.

[0041] The light absorption ability of the catalyst sample in the ultraviolet region was studied by solid UV-visible spectroscopy, and the semiconductor band gap width was obtained using the following formula: (1) Where: is the absorption coefficient, K is a constant, is the frequency, h is Planck's constant, and Eg is the semiconductor bandgap width.

[0042] With h is the horizontal axis, ( h ) 2 As the vertical axis, draw a graph. The value is equal to 1240 divided by the wavelength. The vertical coordinate of the spectrum obtained by the UV-visible diffuse reflectance spectrum is the absorption value Abs. Abs and It is a proportional relationship and will not affect the size of Eg, so the measured Abs can be used instead To represent the vertical coordinate, that is ( bs ) 2 After obtaining the graph, extend the straight line to the horizontal axis. The bandgap width value of the material is the intersection of the straight line and the horizontal axis. The bandgap width graph obtained after processing is as follows: Figure 5 shown.

[0043] Depend on Figure 5 It can be seen that graphene / 4Cu-2Co-MOF has the smallest bandgap and the smallest bandgap.

[0044] In order to explore the adsorption performance of the prepared materials, graphene / 5Cu-1Co-MOF, graphene / 4Cu-1Co-MOF, graphene / 4Cu-2Co-MOF, Cu-MOF, and Co-MOF were tested respectively. In each group of experiments, 50 mg of sample was weighed into a beaker and added to 50 mL of MB solution with a mass concentration of 10 mg / L. The beaker was placed in an air bath constant temperature oscillation box for oscillation at a speed of 500 r / min. 5 ml of solution was taken out at 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, respectively. The solution was placed in a centrifuge tube. After centrifugation in a centrifuge, the supernatant was taken to measure its spectrophotometric removal rate: (2) Where: A 0 —The absorbance corresponding to the MB mass concentration before adsorption reaction; A—absorbance corresponding to the mass concentration of MB at adsorption time t; C 0 —Mass concentration of MB before adsorption; C—Mass concentration of MB corresponding to adsorption time t.

[0045] Test results such as Figure 6 As shown by Figure 6 It can be seen that the graphene-doped copper-cobalt bimetallic MOF composite material with a doping ratio of 4:2 has the fastest adsorption rate, followed by a doping ratio of 4:1. Although the adsorption rates of these two doping ratios are fast, the stability is poor. The doping ratio of 5:1 has strong stability and there is no trend of a decrease in removal rate within 6 hours. The final removal rate of 5:1 is higher than that of the other two ratios, and the 6-hour adsorption rate reaches 89%.

[0046] In order to explore the catalytic degradation performance of the prepared materials, graphene / 5Cu-1Co-MOF, graphene / 4Cu-1Co-MOF, graphene / 4Cu-2Co-MOF, Cu-MOF, and Co-MOF were tested respectively. In each group of experiments, 0.05 g of sample was weighed and placed in a beaker. 100 mL of MB solution with a mass concentration of 10 mg / L was added and stirred in the dark. After 30 minutes, the adsorption / desorption dynamic equilibrium was reached. A 10 W ultraviolet lamp was turned on to simulate visible light irradiation. Photocatalytic experiments were carried out. 5 mL of reaction solution was taken out at 50 minutes, 70 minutes, 90 minutes, 110 minutes, 130 minutes, and 150 minutes respectively. The reaction solution was centrifuged, and the spectrophotometer was used to measure the spectrophotometry of the supernatant. The degradation rate of MB was calculated by the following formula: (3) Where: A 0 —The absorbance corresponding to the MB mass concentration before the degradation reaction; A—absorbance corresponding to the mass concentration of MB at degradation time t; C 0 —Mass concentration of MB before degradation; C—Mass concentration of MB corresponding to degradation time t.

[0047] Test results such as Figure 7 As shown by Figure 7 It can be seen that after 30 minutes of dark reaction, the degradation rates of materials with a copper-cobalt ratio of 4:2 and 4:1 were higher, and the degradation rate of 5:1 was relatively low. After 120 minutes of light reaction, it can be seen that the material with a copper-cobalt ratio of 5:1 had the best degradation effect, degrading 81.3% of methylene blue, and the effect of 4:1 was poor, degrading 76.2% of methylene blue. The poor degradation effect of graphene may be related to the hydrophobicity of graphene. In the degradation experiment, the composite material could not be well dissolved in the methylene blue solution, and the photon utilization rate of graphene was low. In the graphene photocatalytic process, due to its extremely thin structure and strong reflection, the photocatalytic performance was weak and the reaction rate was relatively slow.

[0048] Phenol adsorption experiment: 25 mg of different types of catalysts were added to 50 mL of phenol solution with an initial concentration of 20 mg / L and stirred. 2 mL of samples were taken at certain time intervals and the sample solution was filtered with a 0.22 um water filter. Each group of experiments was repeated three times.

[0049] Phenol catalytic experiment: Add 25 mg of catalyst to 50 mL of phenol solution with an initial concentration of 20 mg / L, stir for 30 min to reach adsorption equilibrium, then add a certain amount of PMS to start the catalytic reaction, sample 1.5 mL at a certain time interval, filter the sample solution with a 0.22 um water filter, and immediately inject 50 uL of methanol. 2 SO 4 Or NaOH solution to adjust pH. Each experiment was repeated three times.

[0050] Figure 8The following is a diagram of the adsorption effect of phenol solutions with different concentrations. The initial concentration of the phenol solution was 20 mg / L, the dosage of various catalysts was 0.5 g / L, and the PMS concentration was 2 mmol / L. The catalytic degradation ability of phenol by different copper-cobalt doped MOF materials was compared under the same experimental conditions. Through the adsorption performance test, we can determine that the copper-cobalt doped series of MOF materials can basically reach adsorption equilibrium or slow adsorption stage within 30 minutes. In order to eliminate the influence of adsorption on the catalytic process, in the subsequent degradation experiment ( Fig. 9 ), all materials were adsorbed in the initial phenol solution for 30 min before PMS was added. After adding 2 mmol / L PMS for 5 min, the phenol concentration in the solution decreased rapidly, and no phenol signal was detected in the 5Cu-1Co graphene MOF material catalyst group at 5 min, indicating that phenol had been completely removed.

[0051] Fig.10 (a) in the figure investigated the degradation performance of 5Cu-1CoMOF material / PMS system on tetracycline at different concentrations, where the catalyst concentration was 0.5 g / L and PMS: 2 mmol / L. Tetracycline is a commonly used broad-spectrum antibiotic with a more complex molecular structure containing multiple phenolic hydroxyl groups, methyl groups and amino groups. The degradation efficiency of 5Cu-1CoMOF material / PMS catalytic system on tetracycline was close to 99% at a concentration of 10 mg / L. When the initial concentration increased to 20 mg / L and 30 mg / L, the degradation efficiency dropped to 94.9% and 86.3%. Fig.10 (b) shows the effect of 5Cu-1CoMOF material / PMS system on the degradation of catechol. When the initial concentration is 10, 20, and 30 mg / L, the degradation efficiency of catechol can reach 100%. It can be seen that for organic matter with more complex structures, the 5Cu-1CoMOF material / PMS system has excellent organic matter degradation performance.

[0052] Fig.11 The catalytic activity of the 5Cu-1CoMOF material / PMS system in complex water quality conditions was investigated. The various influencing factors discussed above were superimposed, and a laboratory simulation was conducted to simulate the presence of phenol, catechol, tetracycline, and interfering ions Cl - , NO 3- , HCO 3- and H 2 PO 4- The 5Cu-1Co@MOF material / PMS system was tested on a solution. After the reaction, the concentrations of the three organic matter in the solution were tested respectively. The maximum removal rates of phenol, catechol and tetracycline by the 5Cu-1Co-MOF material / PMS system were 91.0%, 97.5% and 95.5%, respectively.

[0053] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a copper-cobalt doped graphene MOF composite material, characterized in that: The following steps are involved: Take Co(NO3)2﹒6H2O and Cu(NO3)2 in a molar ratio of (4-5):(1-2), add 0.74g of trimesic acid and 0.1g of graphene, mix and dissolve in 25ml of anhydrous ethanol, stir magnetically at room temperature for 1h, pour into a high-pressure reactor and carry out solvothermal synthesis treatment at 160℃ for 6h, cool and centrifuge, wash the solid after centrifugation twice with DMF and anhydrous ethanol, and obtain graphene / copper-cobalt bimetallic MOF composite material after drying.

2. The method for preparing the copper-cobalt doped graphene MOF composite material according to claim 1, characterized in that: After washing, the mixture was dried at 60°C for 12 h.

3. A copper-cobalt-doped graphene MOF composite material prepared by the method according to claim 1 or 2.

4. An application of the copper-cobalt doped graphene MOF composite material as claimed in claim 3 in the adsorption and photocatalytic degradation of dye wastewater, organic wastewater and antibiotic wastewater.

Citation Information

Patent Citations

  • Dual metallic copper / cobalt metal-organic framework material as well as preparation method and application thereof

    CN109054034A

  • Copper-cobalt double-metal organic framework / nano-fiber composite material, preparation method thereof and application of composite material

    CN109126885A

  • Preparation of 3D graphene-supported CoCu-MOF composite electrocatalyst

    CN109158129A

  • Graphene-doped cobalt-based metal organic framework composite material, preparation method and applications thereof

    CN111013659A

  • Flower-ball-shaped Cu-MOF-74 / GO visible-light-induced photocatalyst and preparation method thereof

    CN112691704A